Transient performances of the gas turbine recuperating waste heat through hydrogen rich fuels. (12th November 2019) - Pan, Fumin; Cheng, Xiaobei; Wu, Xin; Wang, Xin; Luo, Pingping
Abstract: Operational rules and control strategies of the chemically recuperated gas turbine (CRGT) in the marine propulsion are investigated in this paper. The Minimization of Gibbs free energy method is used to calculate the diesel-steam reforming reaction which products synthetic hydrogen rich fuels, and a universal model of the chemical regenerator which is easily applied to different application environments is created. The hydrogen production and hydrogen molar fraction are investigated to verify that the CRGT improve the combustion performances under low working conditions. Off-design calculations are performed to derive proper operational rules, and transient calculations are performed to investigate the best control strategies for the systems. The modelling approach of the chemical regenerator can be generally used in the chemically recuperated gas turbine. The elaborate operational rules can greatly improve the thermal efficiencies under every working condition. The system using synchronous control strategies have better regulation speed and operation stability than that using asynchronous control strategies. Highlights: The hydrogen rich synthetic fuels improve the thermal efficiencies. The elaborate operational rules are propitious to the novel gas turbine cycle. Good synchronous control strategies can be derived through the proposed models. The recovery capacity depends on temperature, steam-to-fuel ratio, and pressure.